Becoming strong : impoverished women and the struggle to overcome violence - Huey, Laura; Broll, Ryan (University of Toronto Press, 2018)
"Drawing on more than 150 in-depth interviews, Becoming Strong: Impoverished Women and the Struggle to Overcome Violence, explores the diverse effects of trauma in the lives of homeless female victims of violence. Laura Huey and Ryan Broll closely examine the negative patterns common to cases of homeless female victims of violence and develop informed solutions for responding to issues that perpetuate cycles of female homelessness. Becoming Strong offers not only a comprehensive examination of trauma and the role it can play in shaping homeless women's lives, but it also explores how women may recover and develop strategies for coping with traumatic experiences."--
Keywords: Homeless women : Violence against : United States; Homeless women : United States : Social conditions; Violence : Psychological aspects; United States